Role of Nuclear Non-Canonical Nucleic Acid Structures in Organismal Development and Adaptation to Stress Conditions - Alecki, Célia; Vera, Maria (Frontiers in Genetics, 2022)
Over the last decades, numerous examples have involved nuclear non-coding RNAs (ncRNAs) in the regulation of gene expression. ncRNAs can interact with the genome by forming non-canonical nucleic acid structures such as R-loops or DNA:RNA triplexes. They bind chromatin and DNA modifiers and transcription factors and favor or prevent their targeting to specific DNA sequences and regulate gene expression of diverse genes. We review the function of these non-canonical nucleic acid structures in regulating gene expression of multicellular organisms during development and in response to different stress conditions and DNA damage using examples described in several organisms, from plants to humans. We also overview recent techniques developed to study where R-loops or DNA:RNA triplexes are formed in the genome and their interaction with proteins.